PEMANFAATAN LAHAN DI BAWAH POHON KELAPA UNTUK HIJAUAN PAKAN SAPI DI SULAWESI UTARA - H.S. Salendu, Artise; H. Elly, Femi (Pastura, 2014)
Cattle in North Sulawesi has a comparative advantage to develop.The problem of low productivity of cattle caused by the provision of forage does not comply with the recommended requirements. Based on these ideas it is necessary to an assessment of the use of land under coconut for forage. Rationale, agriculture in North Sulawesi is dominated by coconut plantation which is the brand image of this area. Cattle development can be implemented with the integrated model under a coconut tree that has not been used optimally. The biggest challenge in the development of cattle in North Sulawesi in general is a matter of the feed. One of the factors that determine the productivity of cattle is ensuring availability of quality forage. Grass quality is introduced to dwarft grass which can produce as much as 288 tons/year, equivalent to 22.5AU/year. Conclusion, cattle development can be done with system of coconut-cattle integration. Land under coconut trees in North Sulawesi can be utilized for the development of cattle forage that can provide greater benefits for farmers. The advice can be given that the necessary interventions to introducing forage quality by utilizing land under coconut.
Keywords: cattle, forage, feed, coconut